School-entry requirements for HPV vaccination: part of the patchwork for HPV-related cancer prevention - Erika L. Thompson; Ellen M. Daley; Tricia Washburn; Kim Salisbury-Keith; Debbie Saslow; Holly B. Fontenot; Gregory D. Zimet (Human Vaccines & Immunotherapeutics, 2021)
Human papillomavirus (HPV) vaccination can prevent six types of HPV-related cancers, and approximately, 54.2% of adolescents are up-to-date with the HPV vaccine in the United States. While moderate success has been achieved with provider- and parent-focused interventions, HPV vaccination in the U.S. lags well behind desired goals. In order to maximize HPV vaccination and prevention of HPV-related cancers, it may be prudent to consider state policy approaches, such as school-entry requirements as part of the patchwork of provider, parent, and structural interventions. In this paper, we reviewed the history of efforts to implement school-entry requirements for HPV vaccine, the challenges and benefits associated with implementing these requirements, and the evidence for the effectiveness of school-entry requirements. In addition, we presented new data from Rhode Island’s Immunization Information System (IIS) showing how their school-entry requirement, implemented in 2015, has impacted HPV vaccination rates. These registry data indicate that HPV vaccination rates improved significantly after the 2014–2015 school year and policy implementation, and add to the ongoing evidence supporting the value of school-entry requirements for HPV vaccination. School-entry requirements should be considered alongside other initiatives and policies for promoting HPV vaccine uptake. Taking a comprehensive systems approach to HPV vaccination is needed.